2022
DOI: 10.1002/chem.202203406
|View full text |Cite
|
Sign up to set email alerts
|

Phospholenes from Phosphabenzenes by Selective Ring Contraction

Abstract: A 3-amino-functionalized phosphabenzene (phosphinine) has been synthesized and structurally characterized. The pyramidalized nitrogen atom of the dimethylamino substituent indicates only a weak interaction between the lone pair of the nitrogen atom and the aromatic phosphorus heterocycle, resulting in somewhat basic character. It turned out that the amino group can indeed be protonated by HCl.In contrast to pyridines, however, the phosphabenzeneammonium salt undergoes a selective ring contraction to form a hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, phospholene ligands are very scarcely applied in transition metal catalysis or as ligands in general [ 20 , 21 ]. Phosphorous chemists have prepared a variety of these molecules over the years [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], primarily using a McCormack cycloaddition between dienes and phosphenium cations. Their main utility has been as precursors to other phosphacycles [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, phospholene ligands are very scarcely applied in transition metal catalysis or as ligands in general [ 20 , 21 ]. Phosphorous chemists have prepared a variety of these molecules over the years [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], primarily using a McCormack cycloaddition between dienes and phosphenium cations. Their main utility has been as precursors to other phosphacycles [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorous chemists have prepared a variety of these molecules over the years [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], primarily using a McCormack cycloaddition between dienes and phosphenium cations. Their main utility has been as precursors to other phosphacycles [ 22 , 23 , 24 , 25 , 26 ]. A secondary phospholene borane precursor to produce 2,5-diarylsubstituted phospholenes was consequently unknown, but was readily prepared in this study by simply omitting the C=C hydrogenation and cis-trans isomerisation steps that were previously used to prepare secondary phospholane borane, 5 [ 10 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 There are several groups of compounds that contain P III and a CP double bond. 5–10 Phosphaalkenes are a special group of these compounds and their chemistry has been developing for almost 50 years. 11,12 Studies revealed that in cases where ( δ −) CP ( δ +) exist, these compounds react with proton-active reagents like hydrogen halides, alcohols, thiols or amines, HX, to give C-protonated congeners C(H)–P(X).…”
Section: Introductionmentioning
confidence: 99%